Influência de determinantes sociais de saúde na saúde bucal da população adulta com idade superior a 50 anos no Brasil - Amaral Júnior, Orlando Luiz do (2020)
The present dissertation was structured by two hypotheses. The first is that different socioeconomic indicators can influence the results presented in oral health research. Therefore, the objective of the first study is to assess the influence of the use of different socioeconomic indicators (individual income, family income per capita and wealth) in oral health research associated with the results “Self-reported oral health (n = 9,365) and Edentulism (n = 9,073) “there is a reduction in the prevalence of individuals who perceive themselves to have poor oral health self-reports and to be edentulous, when compared to the poorest quintiles. The indicators of individual income and family income per capita have been shown to be less sensitive when associated with oral health outcomes. The second hypothesis that involves this dissertation, is that conceptual dimensions (structural and cognitive) of social capital, can influence the oral health self- reported, therefore the aim was to verify associated between social capital considered two conceptual dimensions (Structural and Cognitive) and oral health self- reported. As the outcome we used self-reported oral health (n = 9,365) and as the main predictive variables used four individual social capital variables (Structural: Volunteering and Social Participation), (Cognitive: Trust in the neighborhood residents and Perception of friendship). The results suggest that individuals with less cognitive social capital have a higher prevalence of poor oral health self-reported. The structural dimension was not associated with oral health self-reported. For both studies, data were collected from the Brazilian Longitudinal Study on Aging. The baseline survey was carried out between 2015 and 2016. Were utilized hierarchical models of Poisson regression to have crude and adjusted prevalence ratios. We conclude that the wealth index was the indicator that best identifies the inequalities in oral health in Brazilian adults over 50 years of age. About influence of social capital in oral health self-reported, we ressalted the plausibility of initiatives that promote the development of health policies that stimulate cognitive social capital in society and consequently collaboration with improvements in the oral health of adults aged 50 or over in Brazil.